THE IMPLEMENTATION OF CROSSWORD PUZZLES IN VOCABULARY TEACHING - Pupu Rostina; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2022)
Vocabulary learning is an important and inseparable part of every language learning process for learners. In this research, the implementation of crossword puzzles is considered as an effective way to teach vocabulary to students. Therefore, it is important to make teachers and students familiarized with this relaxed but useful technique. This study intends to describe the process of applying crossword puzzles in vocabulary teaching. This research was carried out at SMP SAIS Soreang Bandung School in class VIII as subjects. Qualitative methods are applied and for triangulation three data collection techniques are chosen such as observation, questionnaire, and interview. Observations were made twice. To complete the data, researchers used observation sheets during the learning process in class. Besides, researchers use learning plans to answer the first research question. To support the data, the results of the questionnaire were analyzed after observation. The interview is conducted with the teacher. The results showed that students were enthusiastic about learning vocabulary through crossword puzzles. Crosswords are good for facilitating thinking and problem-solving. Besides, students also experience increased vocabulary mastery through crossword puzzles. Keywords:  Crossword Puzzles, Vocabulary, Teaching